Impact of obesity and white adipose tissue inflammation on the omental microenvironment in endometrial cancer. Issue 18 (6th July 2022) - Moukarzel, Lea A.; Ferrando, Lorenzo; Stylianou, Anthe; Lobaugh, Stephanie; Wu, Michelle; Nobre, Silvana Pedra; Iasonos, Alexia; Zoppoli, Gabriele; Giri, Dilip D.; Abu‐Rustum, Nadeem R.; Broach, Vance A.; Iyengar, Neil M.; et al.
Abstract : Background: A complex relationship between adipose tissue and malignancy, involving an inflammatory response, has been reported. The goal of this work was to assess the prevalence of white adipose tissue (WAT) inflammation in patients with endometrial cancer (EC), and the association with circulating inflammation markers. Furthermore, the aim was to characterize the pathways activated in and the cell type composition of adipose tissue in patients with EC. Methods: Adipose tissue and blood samples were prospectively collected from 101 patients with EC at initial surgery. WAT inflammation was determined based on adipocytes surrounded by macrophages forming crown‐like structures. Circulating levels of metabolic syndrome–associated and inflammatory markers were quantified. RNA‐sequencing was performed on adipose samples ( n = 55); differential gene expression, pathway, and cellular decomposition analyses were performed using state‐of‐the‐art bioinformatics methods. Results: WAT inflammation was identified in 46 (45.5%) of 101 EC patients. Dyslipidemia, hypertension, and diabetes mellitus were significantly associated with WAT inflammation ( p < .05). WAT inflammation was associated with greater body mass index ( p < .001) and higher circulating levels of leptin, high‐sensitivity C‐reactive protein, and interleukin‐6, as well as lower levels of adiponectin and sex hormone–binding globulin ( p < .05). Transcriptomic analysis demonstrated increased levels of proinflammatory and pro‐neoplastic–related gene expression in inflamed omental adipose tissue. Conclusions: WAT inflammation is associated with metabolic syndrome, obesity, and inflammatory markers, as well as increased expression of proinflammatory and proneoplastic genes. Abstract : Adipose tissue and blood samples were prospectively collected from 101 endometrial cancer patients at initial surgery and approximately half displayed white adipose tissue inflammation, which was associated with metabolic syndrome, obesity, inflammatory markers, and increased expression of proinflammatory and proneoplastic genes. These findings offer new insights into how adipose tissue inflammation correlates with clinical factors in endometrial cancer.